2022
DOI: 10.3389/fbioe.2022.978686
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes through the constructed CRISPR-dcas9 to facilitate the efficient production of O-acetylhomoserine in Corynebacterium glutamicum

Abstract: O-Acetylhomoserine (OAH) is an important platform chemical for the synthesis of L-methamidophos and l-methionine. It has been produced efficiently in Corynebacterium glutamicum. However, a wider range of key factors had not been identified, limiting further increases in OAH production. This study successfully identified some limiting factors and regulated them to improve OAH titer. Firstly, an efficient clustered regularly interspaced short palindromic repeats/dead CRISPR associated protein 9 (CRISPR-dCas9) sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…20 Li et al used a sequential promoter P NCgl2698 to control the expression of the gltA gene and found that the O-acetylhomoserine production could be enhanced. 21 Ma et al reported that the L-valine production increased by 27.3% when the relative transcriptional level of the gltA gene decreased from 1.1 to 0.3. 22 Therefore, the regulation of gene gltA showed to be useful during the biosynthesis process of some amino acids.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Li et al used a sequential promoter P NCgl2698 to control the expression of the gltA gene and found that the O-acetylhomoserine production could be enhanced. 21 Ma et al reported that the L-valine production increased by 27.3% when the relative transcriptional level of the gltA gene decreased from 1.1 to 0.3. 22 Therefore, the regulation of gene gltA showed to be useful during the biosynthesis process of some amino acids.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Over-expression of CS can redirect more carbon flux into the TCA cycle to supply more precursor and energy for cell growth . Li et al used a sequential promoter P NCgl2698 to control the expression of the gltA gene and found that the O -acetylhomoserine production could be enhanced . Ma et al reported that the l -valine production increased by 27.3% when the relative transcriptional level of the gltA gene decreased from 1.1 to 0.3 .…”
Section: Resultsmentioning
confidence: 99%